Production of thermostable pullulanase from Bacillus flavothermus KWF-1: medium development using experimental design with data transformation - Abu Samah, Rozaimi (Penerbit UTM Press, 2008)
The extracellular production of pullulanase from Bacillus flavothermus KWF-1 using experimental design was studied. Two-level full factorial design was applied to enhance these nutrient constituents with respect to pullulanase production. Statistical analysis (ANOVA) have identified that tapioca starch was the most significant factor affecting the enzyme production. Diagnostic plots obtained from ANOVA revealed abnormalities with respect to the response data. Therefore, data transformation was advantageous in order to make the distribution of the response variable closer to the normal distribution and to stabilize the variance of the response, as well as to improve the fit of the model to the data. An improved model was attained with higher coefficient of determination (R2 = 0.9523) compared to original R2 of 0.9280. The enhanced medium consisted of (% w/v): 3.0 tapioca starch, 0.11 peptone from casein, 0.08 KH2PO4, 0.02 MnSO4 and an initial pH of 9.0, produced 3.498 U/ml pullulanase, which was approximately 4.5 fold increment than that obtained from initial medium (0.791 U/ml).